Correction to: Inhibition of autophagy enhances synergistic effects of Salidroside and anti-tumor agents against colorectal cancer - Hai Li; Chen Chen (BMC, 2018)
Correction The authors of this article [1] would like the funding and acknowledgements to be disregarded.